If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6) = 3(x) Multiply 2 * 6 12 = 3(x) Solving 12 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 12 + -3x = 0 Add '-12' to each side of the equation. 12 + -12 + -3x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = 0 + -12 -3x = 0 + -12 Combine like terms: 0 + -12 = -12 -3x = -12 Divide each side by '-3'. x = 4 Simplifying x = 4
| 4x^2+2x-10=0 | | -16-6w=-34 | | 18x=3x+210 | | -.75(8x-4)=.125(-4x+8) | | a=-7.1-2.1(4) | | 6x-2(x+4)=-38-2x | | 2+4x=-(-4-3x)+1 | | (7y-5)+(6-5y)=23 | | 5(3x-4)-3=15 | | e^4x=32 | | 8n-(3n+5)=5 | | 2+4x=-(4-3x)+1 | | a=-7.1-2.1(3) | | 20=9-x | | 15x-8=10+9 | | a=-7.1-2.1(2) | | 2+4x=-(-3x)+1 | | -5=3x-17 | | -8-4(5-8k)=164 | | 17x-29y=19 | | -8-4(5-8k)= | | -3x+5+5x=-3 | | -5(12-20)+(6-10)= | | -18+8=-2(x+8) | | 6x+8+4x+10= | | x^2+21x+68=0 | | 9x^2-9x-10=10 | | 6x+6x-12-5x+5x+15=-20 | | 5x+20(x-2)=210 | | 0.35(c-5)=0.45(c+4) | | 3x+15=x+14 | | x^6-2x^5-8x^4+14x^3+11x^2-28x+12=0 |